2021
DOI: 10.1101/2021.05.27.445469
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamics of repair and regeneration of adult zebrafish respiratory gill tissue after cryoinjury.

Abstract: The study of respiratory tissue damage and repair is critical to understand not only the consequences of respiratory tissue exposure to infectious agents, irritants and toxic chemicals, but also to comprehend the pathogenesis of chronic inflammatory lung diseases. To gain further insights into these processes, we developed a gill cryoinjury model in the adult zebrafish. Time course analysis showed that cryoinjury of the gills triggered an inflammatory response, extensive cell death and collagen deposition at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 76 publications
0
1
0
Order By: Relevance
“…Cryoinjury is popular in heart regeneration studies in both zebrafish (Gonzalez-Rosa et al, 2011;Schnabel et al, 2011;Dyck et al, 2020) and medaka (Lai et al, 2017) as it mimics the myocardial infarction in mammals better than resection model (Chablais et al, 2011;Darehzereshki et al, 2015). This technique can also be applied to external organs, such as the fin (Chassot et al, 2016) and gills (Ramel et al, 2021). However, cauterization is technically challenging and less reproducible compared to resection.…”
Section: Injury Modelsmentioning
confidence: 99%
“…Cryoinjury is popular in heart regeneration studies in both zebrafish (Gonzalez-Rosa et al, 2011;Schnabel et al, 2011;Dyck et al, 2020) and medaka (Lai et al, 2017) as it mimics the myocardial infarction in mammals better than resection model (Chablais et al, 2011;Darehzereshki et al, 2015). This technique can also be applied to external organs, such as the fin (Chassot et al, 2016) and gills (Ramel et al, 2021). However, cauterization is technically challenging and less reproducible compared to resection.…”
Section: Injury Modelsmentioning
confidence: 99%
“…An additional future direction for evaluation of biopsy would be an extension of the monitoring period in order to assess biopsy through all stages of healing. Although previous research (Zhao et al 2014;McCormick 1993) noted that cuts from gill biopsies were found to be fully healed within 7 days of biopsy, the time required to regenerate tissue lost may exceed 40 days (as identified in the model species Danio rerio) (Ramel et al 2021). Furthermore, muscle biopsies have been noted to fully healed in Smallmouth Bass within two months of biopsy (Ackerson et al 2014).…”
Section: Tablesmentioning
confidence: 99%